Impact Of The Home Bleaching On Shear Bond Strength Of Orthodontically Bonded Teeth - Karamshetty, Akhil; Lahoti, Seema; Choudhary, Gurubachan Singh; Kardam, Kirti; Singh, Gargi; Lakadkutta, Ahad (Journal of Neonatal Surgery, 2025)
Objective: To evaluate the impact of various home bleaching agents on shear bond strength of orthodontic brackets. Materials and Methods: A total of 45 premolars were randomly divided into three groups of 15 each. GROUP-A has 15 sound human premolars which were not bleached before bonding (control group), GROUP-B has 15 sound human premolars which were bleached with 16 % carbamide peroxide bleaching agent, GROUP-C has 15 sound human premolars which were bleached with 35% carbamide peroxide bleaching agent. An LED light was used to cure the light-cured composite resin that was used to bond the orthodontic brackets. Following bonding, a Universal testing machine was used to test the brackets' SBS. Result: The mean bond strength in Group A was 293.39±61.48 while in Group B was 153.65±16.63 and in Group C was 56.18±24.72. One way ANOVA test was applied. The test result showed statistically highly significant difference between groups with F value 136.98 and P value 0.001. The SBS of Group A is significantly higher than Group B and Group C, while the SBS of Group C is the least of all the three groups. Conclusion: The SBS of orthodontic brackets on human enamel was considerably decreased by both home bleaching agents.